Lossless quartz crucible surface layer purity detection method
Through the lossless quartz crucible surface purity detection method, the etching solution and chemical digestion technology are used to solve the problem that quartz crucible cannot be reused after detection in the prior art, and the effective utilization of resources and high-precision detection are achieved.
Patent Information
- Application Number
- CN202411508003.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the surface purity detection of quartz crucibles adopts permanent destructive tests, which leads to the inability to use the quartz crucibles again and causes waste of resources.
The surface purity detection method of the non-destructive quartz crucible was used to contact the surface etching solution with the surface quartz crucible, and the etched solution and residue were collected for chemical digestion, and the content of impurities in the digested solution was detected, and the purity of the surface quartz crucible was calculated.
The surface purity detection of the quartz crucible is achieved, and the waste of resources is avoided. The surface of the detected quartz crucible is not damaged and can still be used.
Smart Images

Figure CN119492725A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor manufacturing component purity testing technology, specifically relating to a non-destructive method for testing the purity of the surface layer of a quartz crucible. Background Technology
[0002] The purity of the surface layer of a quartz crucible is related to the quality of products in the downstream industry chain. Currently, quartz crucibles are mainly made by melting high-purity quartz sand using a high-temperature electric arc method. However, factors such as an unclean working environment during the melting process or the purchase of high-purity quartz sand mixed with lower-grade quartz sand by the manufacturer will affect the purity of the quartz crucible.
[0003] Poor surface purity of quartz crucibles can easily lead to crystallization during the crystal rod production process. Severe crystallization can cause crucible deformation and silicon leakage. In addition, regardless of whether crystallization occurs in the quartz crucible, crystal rods drawn from quartz crucibles with poor surface purity are of poor quality, and their crystal form and purity have been altered. Furthermore, with changes in the market environment and technological advancements, the market demands increasingly higher surface purity for quartz crucibles, forcing quartz crucible manufacturers to strictly control their surface purity.
[0004] Currently, the purity of the surface layer of quartz crucibles is tested using a permanent destructive test, which involves cutting a portion of the quartz crucible surface with a cutting tool for purity testing. The tested quartz crucible cannot be used again, which causes great losses and waste of resources for producers. Summary of the Invention
[0005] In view of this, the present invention provides a non-destructive method for detecting the purity of the surface layer of a quartz crucible, in order to solve the technical problem in the prior art that the purity of the surface layer of a quartz crucible is tested only by a permanent destructive test, and the quartz crucible cannot be used after the test, which causes great losses and waste of resources to the producers.
[0006] To achieve the above objectives, this application adopts the following approach:
[0007] A non-destructive method for detecting the purity of the surface layer of a quartz crucible includes the following steps:
[0008] S10. Select the etching solution and the quartz crucible to be tested;
[0009] S20. The etching solution is brought into contact with the surface of the quartz crucible for a preset etching time, wherein the ratio of the volume of the etching solution to the etching area of the quartz crucible surface is 1 mL:(5 to 6) cm². 2 ;
[0010] S30. After etching is completed, collect the etching solution and the residue on the surface of the quartz crucible, and rinse the surface of the quartz crucible with pure water 3 to 5 times. Collect the rinsing liquid, take a certain amount of the rinsing liquid and mix it with the collected etching solution and the residue on the surface of the quartz crucible, and chemically digest the mixture to obtain a digestion solution. The volume of the digestion solution is the same as the volume of the etching solution in S20.
[0011] S40. Detect the content of each impurity element in the digestion solution, and calculate the purity of the quartz crucible surface layer based on the detected content of each impurity element.
[0012] Preferably, the purity of the quartz crucible surface layer is calculated based on the detected content of each impurity element using the following formula:
[0013] W = (1-L) × 100%
[0014] Wherein: W: SiO2 content in the surface layer of the quartz crucible, in wt%; L: content of various impurity elements in the surface layer of the quartz crucible, in ug / g.
[0015] Preferably, the content of each impurity element on the surface of the quartz crucible is calculated using the following formula:
[0016]
[0017] Where: L: content of each impurity element on the surface of the quartz crucible, in ug / g; C: value of each impurity element tested, in ug / mL; V: volume of digestion solution, in mL; m: mass of the quartz crucible surface etched, in g.
[0018] Preferably, m is calculated using the following formula:
[0019] m=S×20um×P
[0020] Where: S: Surface area of the etched quartz crucible, in cm² 2 P: Density of the quartz crucible, in g / cm³ 3 .
[0021] Preferably, the etching solution is a hydrofluoric acid solution with a mass concentration of 22% to 27%.
[0022] Preferably, the preset duration is 80 to 100 minutes.
[0023] Preferably, the etching solution is brought into contact with the surface R portion of the quartz crucible for a preset etching time, specifically including: determining the etching area of the surface R portion of the quartz crucible, and applying paraffin wax to the quartz crucible surface outside the etching area for 1 mm to 3 mm, in order to prevent the hydrofluoric acid solution from splashing and corroding other parts of the quartz crucible surface when the hydrofluoric acid solution is poured into the R portion.
[0024] The technical solution adopted in this application can achieve the following beneficial effects:
[0025] This invention provides a non-destructive method for detecting the purity of the quartz crucible surface. A selected etching solution is brought into contact with the surface of the quartz crucible to be tested for a preset etching time. The etching solution corrodes the surface of the quartz crucible. The etching solution and the residue on the quartz crucible surface are collected and chemically digested to obtain a digestion solution. The volume of the digestion solution is ensured to be the same as the volume of the etching solution before etching. The content of each impurity element in the digestion solution is detected, and the purity of the quartz crucible surface is calculated based on the detection results. The etched quartz crucible surface is smooth and colorless, and its surface roughness meets product requirements. Compared with the existing technology that uses a cutting tool to cut a portion from the surface of the quartz crucible for purity testing, the method provided in this application does not damage the surface of the quartz crucible after purity testing, allowing it to remain usable, effectively saving resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of etching the surface R region of a quartz crucible using hydrofluoric acid solution in Embodiment 1 of this application. Detailed Implementation
[0027] To facilitate understanding of this application, a more comprehensive description will be provided below with reference to the accompanying drawings. Preferred embodiments of this application are also given. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to enable a more thorough and complete understanding of the disclosure of this application.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0029] In this embodiment, a non-destructive method for detecting the purity of the surface layer of a quartz crucible includes the following steps:
[0030] S10. Select the etching solution and the quartz crucible to be tested;
[0031] S20. The etching solution is brought into contact with the surface of the quartz crucible for a preset etching time, wherein the ratio of the volume of the etching solution to the etching area of the quartz crucible surface is 1 mL:(5 to 6) cm². 2 ;
[0032] S30. After etching is completed, collect the etching solution and the residue on the surface of the quartz crucible, and rinse the surface of the quartz crucible with pure water 3 to 5 times. Collect the rinsing liquid, take a certain amount of the rinsing liquid and mix it with the collected etching solution and the residue on the surface of the quartz crucible, and chemically digest the mixture to obtain a digestion solution. The volume of the digestion solution is the same as the volume of the etching solution in S20.
[0033] S40. Detect the content of each impurity element in the digestion solution, and calculate the purity of the quartz crucible surface layer based on the detected content of each impurity element.
[0034] During testing, firstly, the etching solution is selected. If the mass concentration of the hydrofluoric acid solution is too high, it will damage the surface of the quartz crucible; if the mass concentration is too low, it will not be able to etch sufficiently. Therefore, the etching solution is preferably a hydrofluoric acid solution with a mass concentration of 22% to 27%. The surface of the quartz crucible to be tested is wiped clean. The purity test area on the surface of the quartz crucible can be any area. In this embodiment, it is preferable to contact the etching solution with the R-section of the quartz crucible surface for a preset etching time, specifically including: determining the etching of the R-section of the quartz crucible surface. The surface of the quartz crucible outside the etched area is coated with paraffin wax to a thickness of 1 mm to 3 mm. This is to prevent splashing hydrofluoric acid solution from corroding other parts of the quartz crucible surface when the hydrofluoric acid solution is poured into the R-section. The surface purity of the quartz crucible, melted using a high-temperature arc method, is the worst compared to the surface purity of the straight arm and bottom. Furthermore, the R-section of the quartz crucible, due to its curved design, is very suitable for holding the hydrofluoric acid solution, demonstrating representativeness and feasibility. The etching solution volume and etching area are then poured into the quartz crucible according to the aforementioned ratio. The R-region is etched at room temperature and pressure for a preset time, for example, 80 to 100 minutes. Etching beyond 100 minutes will damage the surface of the quartz crucible. If the etching time is less than 80 minutes, the etching is insufficient, resulting in too little collected etched material and inaccurate detection. After etching, all the hydrofluoric acid solution in the quartz crucible is transferred to a container, and the etched R-region is rinsed multiple times with pure water, for example, 3 to 5 times, to obtain a rinsing solution. This rinsing solution can be precipitated, and a certain amount of the bottom rinsing solution and precipitate is taken. The etching solution to be tested is transferred to a container. This etching solution is then chemically digested, and the resulting solution is diluted to a final volume and shaken to obtain a digestion solution. This process serves two purposes: firstly, it ensures thorough collection of etching residue from the R region of the quartz crucible, leading to more accurate data; secondly, it guarantees that the volume of the digestion solution is the same as the volume of the etching solution before testing, resulting in more accurate calculations. Furthermore, rinsing the etched area removes the hydrofluoric acid solution without damaging it. The content of each impurity element in the digestion solution is tested using inductively coupled plasma atomic emission spectrometry (ICP-AES) or mass spectrometry. Based on the test results, the concentration of the surface layer of the quartz crucible is calculated using the following formula:
[0035] W = (1-L) × 100%
[0036] Wherein: W: SiO2 content in the surface layer of the quartz crucible, in wt%; L: content of various impurity elements in the surface layer of the quartz crucible, in ug / g.
[0037] In some preferred embodiments, the content of each impurity element on the surface of the quartz crucible is calculated using the following formula:
[0038]
[0039] Where: L: content of each impurity element on the surface of the quartz crucible, in ug / g; C: value of each impurity element tested, in ug / mL; V: volume of digestion solution, in mL; m: mass of the quartz crucible surface etched, in g.
[0040] Furthermore, m is calculated using the following formula:
[0041] m=S×20um×P
[0042] Where: S: Surface area of the etched quartz crucible, in cm² 2 P: Density of the quartz crucible, in g / cm³ 3 .
[0043] The etched quartz crucible has a smooth surface with no color difference, and its surface roughness meets product requirements. Compared with the existing technology that uses a cutting tool to cut a portion of the quartz crucible surface for purity testing, the method provided in this application does not damage the surface of the quartz crucible after the purity test, and it can still be used, effectively saving resources.
[0044] The following specific experimental examples further illustrate the technical solution and effects of the present invention. It should be noted that the following experimental examples are only for further explanation of the present invention and do not limit the technical solution of the present invention.
[0045] 1. Blank example 1
[0046] Prepare a quartz crucible to be tested. Use a cutting instrument to cut a portion from the R part of the quartz crucible as the sample to be tested. Chemically digest the sample according to the existing digestion methods. After digestion, use inductively coupled plasma atomic emission spectrometry (ICP-AES) to detect the elements in the digested sample. Input the detected data into intelligent analysis software for data processing and analysis to obtain the purity of the quartz crucible surface. The results are shown in Table 1.
[0047] 2. Example 1
[0048] The quartz crucible used in this Example 1 is made from the same raw materials as the quartz crucible in Blank Example 1 above, and was produced in the same batch. Figure 1 As shown, the quartz crucible is placed at an angle in a well-ventilated and clean place. A 15 mL volume of 25% hydrofluoric acid solution is slowly poured into part R of the crucible, with a contact area of 75 cm² between the hydrofluoric acid solution and part R. 2The solution was allowed to stand for 60 minutes. After standing, all the hydrofluoric acid solution in the quartz crucible was transferred to a volumetric flask to obtain an etching solution. The etched area at part R of the quartz crucible was then rinsed five times with pure water, and all the rinsing solution was transferred to a volumetric flask. The etching solution was then chemically digested to obtain a digested solution, which was then diluted to volume and shaken well. The content of each impurity element in the test solution was tested using an inductively coupled plasma optical emission spectrometer. Based on the test results, the purity of the quartz crucible surface layer was calculated using the above formula. The results are shown in Table 1.
[0049] Table 1 Data Detection Table for Blank Example 1 and Example 1
[0050]
[0051] As can be seen from the data in Table 1 above, Example 1 uses the method provided in this application to detect the purity of the quartz crucible surface. Compared with the method of detecting the purity of the quartz crucible surface in the prior art in Blank Example 1, the accuracy of the detection is almost the same. In addition, the quartz crucible in Example 1 is undamaged after detection and can still be used, thus avoiding waste of resources.
[0052] 3. Example 2
[0053] The difference between Example 2 and Example 1 is that the contact area between the hydrofluoric acid solution and the R-site is changed. When the volume of the hydrofluoric acid solution is 15 mL and the mass concentration is 25%, the contact area between the hydrofluoric acid solution and the R-site is 60 cm². 2 90cm 2 105cm 2 Three quartz crucibles identical to those in Example 1 were used for testing, with other steps identical to those in Example 1. After the tests, the surface purity of each quartz crucible was calculated, and the results are shown in Table 2.
[0054] Table 2 Data Detection Table for Example 2
[0055]
[0056] The data in Table 2, combined with those in Table 1, clearly demonstrate that when the volume of the hydrofluoric acid solution is 15 mL and its mass concentration is 25%, the contact area between the hydrofluoric acid solution and part R is 60 cm². 2 While this method can detect the purity of the quartz crucible's surface, it also causes slight damage to the surface. The contact area between the hydrofluoric acid solution and part R is 90 cm². 2 At that time, the effect was the same as that in Example 1 above; the contact area between the hydrofluoric acid solution and the R part was 105 cm². 2At that time, the purity of the quartz crucible surface obtained by detection differed greatly from that of the quartz crucible surface in Blank Example 1 and Example 1. This may be because the volume of the hydrofluoric acid solution was too small to fully etch the surface of the quartz crucible, thus failing to adequately detect impurity elements. This resulted in a high purity of the quartz crucible surface, which was not precise enough. Therefore, when the volume of the hydrofluoric acid solution was 15 mL and the mass concentration was 25%, the contact area between the hydrofluoric acid solution and the R part was 75 cm². 2 and 90cm 2 The effect is better at that time.
[0057] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.
Claims
1. A non-destructive method for detecting the purity of the surface layer of a quartz crucible, characterized in that: The following steps are involved: S10. Select an etching solution and a quartz crucible to be tested; S20. The etching solution is brought into contact with the surface of the quartz crucible for a preset etching time, and the ratio of the volume of the etching solution to the etching area of the surface of the quartz crucible is 1 mL: (5 to 6) cm 2 ; S30. After etching is completed, the etching solution and the residue on the surface of the quartz crucible after etching are collected, and the surface of the quartz crucible is rinsed with pure water 3 to 5 times, the rinse liquid is collected, a certain amount of the rinse liquid is mixed with the collected etching solution and the residue on the surface of the quartz crucible, and the mixture is chemically digested to obtain a digestion solution, the volume of the digestion solution is the same as the volume of the etching solution in S20; S40. Detecting the content of each impurity element in the digestion solution, and calculating the purity of the surface layer of the quartz crucible according to the detected content of each impurity element.
2. The non-destructive quartz crucible surface purity detection method according to claim 1, characterized in that: The purity of the surface layer of the quartz crucible is calculated according to the detected content of each impurity element by the following formula: W=(1-L)×100% Where: W: SiO2 element content on the surface of the quartz crucible, unit: wt%; L: The content of impurity elements on the surface of the quartz crucible, unit: ug / g.
3. The non-destructive quartz crucible surface purity detection method according to claim 2, characterized in that: The content of each impurity element on the surface of the quartz crucible is calculated by the following formula: Where: L: content of each impurity element on the surface of quartz crucible, unit: ug / g; C: Test value of each impurity element, unit: ug / mL; V: volume of digestion solution, unit: mL; m: The mass of the quartz crucible surface etched, unit: g.
4. The non-destructive quartz crucible surface purity detection method according to claim 3, characterized in that: The m is calculated by the following formula: m=S×20um×P Where: S: etched quartz crucible surface area, unit: cm 2 ; P: Quartz crucible density, unit: g / cm 3 .
5. The non-destructive quartz crucible surface purity detection method according to claim 1, characterized in that: The etching solution is a hydrofluoric acid solution with a mass concentration of 22% to 27%.
6. The non-destructive quartz crucible surface purity detection method according to claim 1, characterized in that: The preset duration is 80 minutes to 100 minutes.
7. The non-destructive quartz crucible surface purity detection method according to claim 1, characterized in that: The etching solution is brought into contact with the R portion of the surface layer of the quartz crucible for a preset etching time, specifically comprising: determining the etching area of the R portion of the surface layer of the quartz crucible, and coating the surface layer of the quartz crucible outside the etching area with paraffin wax by 1 mm to 3 mm to prevent the splashing of the hydrofluoric acid solution to corrode other parts of the surface layer of the quartz crucible when the hydrofluoric acid solution is transferred to the R portion.
Citation Information
Patent Citations
Purification method for in-situ generation of universe cause nuclide granite chronology sample
CN114518280A
Method for etching surface of quartz crucible
CN118307211A
Evaluation equipment for pickling quartz crucible
CN213600530U
Cleaning and recovery of impurity on inner surface of quartz crucible
JP1993105574A
Method of impurity analysis of quartz crucible and impurity recovery jig used for the same
JP2019066262A